Alcatel-Lucent Service Routing Architect (SRA) self-study guide : preparing for the BGP, VPRN and Multicast exams - Warnock, Glenn; Ghafary, Mira; Shaheen, Ghassan; Alcatel-Lucent (Firm) (Indianapolis, IN : Wiley, 2015)
A comprehensive resource for professionals preparing for Alcatel-Lucent Service Routing Architect (SRA) certification Networking professionals are taking note of Alcatel-Lucent and its quick ascent in the networking and telecom industries. IP networking professionals looking for a comprehensive guide to obtaining the Alcatel-Lucent Service Routing Architect (SRA) certification will be pleased to learn of this new publication, Alcatel-Lucent Service Routing Architect (SRA) Self-Study Guide: Preparing for the BGP, VPRN and Multicast Exams. The book comprises approximately 2,600 pages of print a.
Import Policy with Prefix-ListMatching on Prefix Length; 5.3 Using Communities to Control Route Selection; Use of the Community Attribute; 5.4 Aggregate Route Policy; Advertising Aggregate and Specific Routes; Advertising Aggregate Route Only; Aggregating Neighboring AS Address Space; 5.5 Using AS-Path to Control Route Selection; AS-Path Prepend; AS-Path Regular Expressions; 5.6 Using MED; always-compare-med; 5.7 Using Local-Pref to Influence Traffic Flow; Practice Lab: Configuring BGP in SR OS; Lab Section 5.1: Defining Communities; Lab Section 5.2: Build the Inter-AS Export Policies
Includes index.
Online resource; title from PDF title page (Ebsco, viewed May 1, 2015).
Keywords: Routing (Computer network management) -- Examinations -- Study guides; Electronic data processing personnel -- Certification -- Study guides; COMPUTERS / Networking / Network Protocols; COMPUTERS / Certification Guides / General; Electronic data processing personnel -- Certification -- Study guides; Electronic data processing personnel -- Certification; Routing (Computer network management) -- Examinations -- Study guides; Routing (Computer network management) -- Examinations; Electronic books; Electronic books